Measurement and understanding in science and humanities: interdisciplinary approaches - Schweiker, Marcel; Haß, Joachim; Novokhatko, Anna A.; Halbleib, Roxana (Springer Fachmedien Wiesbaden, 2023)
Benefits and challenges of interdisciplinary work -- Examples of interdisciplinary work to measure and understand the world -- Communication of interdisciplinary work -- Success factors and conclusions -- Similarities and differences in the meaning of number and measure between disciplines.